Larvicidal potential of mimusops elengi against aedes aegypti (L) and Culex quinquefasciatus (Say) - Ruikar, Anjali D.; Pawar, Pushpa V.; Sen, Avalokiteswar; Phalgune, Usha D.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Journal of Vector Borne Diseases, 2012)
Keywords: Aedes aegypti; Culex quinquefasciatus; larvicidal activity; Mimusops elengi

Lavandula gibsoni and plectranthus mollis essential oils: chemical analysis and insect control activities against aedes aegypti, anopheles sfttephensi and culex quinquefasciatus - Kulkarni, Roshan R.; Pawar, Pushpa V.; Joseph, Mary P.; Akulwad, Ambadas K.; Sen, Avalokiteswar; Joshi, Swati P. (Journal of Pest Science, 2013)
Essential oils and acetone extracts from Lavandula gibsoni and Plectranthus mollis, family Lamiaceae, were investigated for their mosquito larvicidal activity against 4th instar larvae of Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus. LC50 values against these three species were 48.3, 62.8 and 54.7 mg/L for L. gibsoni essential oil and 118.5, 137.2 and 128.1 mg/L, respectively, for its acetone extract, while LC50 values for P. mollis essential oil were 25.4, 33.5 and 29.5 mg/L and 195.0, 213.8 and 209.0 mg/L, respectively, for its acetone extract. Repellence of the essential oils was assessed against A. aegypti adults. L. gibsoni essential oil provided 100 % protection for more than 7 h at a concentration of 2.0 mg/cm(2). Under the same conditions, the standard repellent N,N-diethyl-meta-toluamide, at 0.25 mg/cm(2), provided 100 % protection for more than 8 h, while P. mollis essential oil was only weakly repellent. The major components from both essential oils were identified based on GC-MS analysis and linear retention indices. Our results demonstrated promising larvicidal activities of both essential oils against these mosquito species. L. gibsoni essential oil also showed promising repellent activity.
Keywords: Essential oil; Lavandula gibsoni; Mosquito larvicidal activity; Mosquito repellent; Plectranthus mollis

Parasitism by Chelonus blackburni (Hymenoptera) affects food consumption and development of Helicoverpa armigera (Lepidoptera) and cellular architecture of the midgut - Sanap, Yogita; Dawkar, Vishal V.; Giri, Ashok P.; Sen, Avalokiteswar; Pandit, Radhakrishna S. (Journal of Asia-Pacific Entomology, 2016)
Biological control agents are vital components of an integrated pest management strategy, and this is frequently referred to as natural control. Natural enemies of insect pests include predators, parasitoids, and pathogens. Among them, a parasitoid, Chelonus blackburni (Cameron), was found to be the best biological control agent for the polyphagous pest, Helicoverpa armigera (Hubner). C. blackburni alters the feeding performance of H. annigera larvae upon parasitism and as a result severely affects growth and development. Moreover, it shortens the feeding period of H. armigera and increases mortality. Furthermore, total hemocyte count (THC) was significantly decreased in parasitized larvae than control. Parasitized H. armigera had 26% less number of blood cells compared to healthy larvae. Histological studies showed that the structure of midgut of H. annigera is drastically affected by C. blackburni leading to reduced food consumption, which ultimately led to larval death. The present study provides an insight to changes involved in H. annigera due to parasitism by C blackburni, a parasite that could be used as an effective biocontrol agent to manage H. armigera. (C) 2015 Korean Society of Applied Entomology, Taiwan Entomological Society and Malaysian Plant Protection Society. Published by Elsevier B.V. All rights reserved.

Biology and development of xanthopimpla pedator (hymenoptera: ichneumonidae): pupal endoparasitoid of antheraea mylitta (Lepidoptera: Saturniidae) - Gathalkar, Ganesh B.; Barsagade, Deepak D.; Sen, Avalokiteswar (Annals of the Entomological Society of America, 2017)
The Antheraea mylitta (Drury) (Lepidoptera: Saturniidae) is a commercially important species for the production of tasar silk. However, the Xanthopimpla pedator (F.) (Hymenoptera: Ichneumonidae) is a major pupal endoparasitoid of A. mylitta, which affects the total tasar silk production in India. A gravid female X. pedator parasitizes the pupae of A. mylitta by depositing an egg, which produces a single offspring per host. We studied the development of immature forms of X. pedator by dissecting parasitized pupae of A. mylitta under laboratory conditions at 28-30 degrees C and 40-60% relative humidity. All immature stages of the parasitoid develop within the host in 20-22 d, by devouring the entire pupal content, resulting in dead or seedless cocoons. The total life cycle of X. pedator is completed inside the host pupa and the adult emerges out by rupturing the peduncle end of the cocoon. During development of X. pedator, five preimaginal stages, viz., egg, larval instars, prepupa, pupa, and a pharate adult, were observed. Xanthopimpla pedator passes through five larval instars identified by structural and morphometric variations. These include primary larva (L1), the intermediate larvae (L2-L4), and the finalinstar larva (L5). Biometric study and larval head width permitted the morphological separation of all five larval instars. In the present study, the biology and development of X. pedator inside the pupa of A. mylitta are reported for the first time with detailed photomicrographs. Therefore, the study may enable the information concerning physiological interactions between A. mylitta and its endoparasitoid, X. pedator.

Identification of a novel series of potent organosilicon mosquito repellents - Kulkarni, Akshay S.; Ramesh, Remya; Walia, Safal; Sayyad, Shahebaz I.; Gathalkar, Ganesh B.; Balamkundu, Seetharamsing; Joshi, Manali; Sen, Avalokiteswar; Reddy, D. Srinivasa (ACS Omega, 2021)
Mosquito control by personal protection is one of the most efficient ways of curtailing deadly diseases such as malaria and dengue with the potential to save millions of lives per year. DEET (N,N-diethyl-3-methyl benzamide) is currently considered as the gold standard for mosquito repellents, being used for the past several decades. Control by DEET, however, is being threatened by emerging resistance among mosquitoes. To address this concern and also to improve protection times, we synthesized a novel series of 25 silicon-containing acyl piperidines using acid–amine coupling protocol and tested their activity against Aedes aegypti in mosquito-repellent assays. Several compounds from this series appear to possess good mosquito-repellent properties. Most notably, at 0.5 mg/cm2 concentrations, the mean protection time for NDS100100 was 756 min, which was higher than that of DEET (616 min). The details of design, synthesis, and biological evaluation are discussed herein.